Peranan Raja Faisal Bin Abdul Aziz Al-Saud dalam Mempertahankan Kedaulatan Wilayah Palestina (1930-1975) - Diman, Muhammad Wardiman; Susmihara; Suraya Rasyid; Abu Haif (Universitas Islam Negeri Alauddin Makassar, 2024)
Penelitian ini mengkaji peran seorang tokoh dengan judul